Correlation Between Learning and Memory Impairment and Changes in Cerebral White Matter Nerve Fibers and Pericytes in Rats with Chronic Cerebral Ischemia - HUANG Jia; WANG Mengxue; NI Jinglei; LIANG Shengxiang; LIN Bingbing (康复学报)
ObjectiveTo analyze the correlation between the changes of learning and memory and the progressive degeneration of white matter nerve fibers and pericytes in the corpus callosum and hippocampus of rats with chronic cerebral ischemia, then to explore the mechanism of learning and memory impairment caused by chronic cerebral ischemia, and provide a possible predictive target for vascular cognitive impairment.MethodsA total of 24 SPF male SD rats were divided randomly into sham operation group, 28 days after operation group and 56 days after operation group, with eight rats in each group. The sham operation group were treated with bilateral common carotid arteries separation without ligation, and chronic cerebral ischemia models were established by ligation of bilateral common carotid arteries in the 28 days after operation group and the 56 days after operation group. At 28 d and 56 d after operation, morris water maze was used to detect spatial learning and memory ability; diffusion tensor imaging was used to observe the fractional anisotropy (FA) and mean diffusivity (MD) rate of white matter nerve fibers in corpus callosum and hippocampus; luxol fast blue (LFB) staining was used to observe demyelination in corpus callosum; Western blot was used to detect the expression of myelin basic protein (MBP) and pericyte marker platelet-derived growth factor receptor β (PDGFR-β) in corpus callosum and hippocampus.Results(1) Learning and memory ability: compared with the sham operation group, the escape latency prolonged significantly from day 2 to day 4 after operation in the 28 days after operation group and on the 3rd day in the 56 days after operation group (P<0.05). Compared with the sham operation group, the times of crossings of the platform and the proportion of target quadrant time in the 28 days after operation group and the 56 days after operation group were significantly lower (P<0.05). (2) Changes of white matter nerve fibers in corpus callosum and hippocampus: compared with the sham operation group, the MD values of white matter nerve fibers in the left and right corpus callosum and the left and right hippocampus in the 28 days after operation group and the 56 days after operation group were significantly lower (P<0.05). (3) Correlation analysis between learning and memory ability and MD values of corpus callosum or hippocampus: there was a positive correlation between the times of crossings of the platform and MD values of corpus callosum or hippocampus (r=0.832, P<0.01; r=0.777, P<0.01). (4) Morphology of nerve fibers in the corpus callosum: compared with the sham operation group, the structure disorder and loss of myelin sheath occurred in the corpus callosum after chronic cerebral ischemia. The grade of myelin disorder in the 28 days after operation group and the 56 days after operation group was significantly higher (P<0.05). (5) Expression of MBP and PDGFR-β protein in corpus callosum and hippocampus: compared with the sham operation group, the expression of myelin basic protein in the corpus callosum and hippocampus decreased significantly in the 28 days after operation group and the 56 days after operation group (P<0.05). The expression level of PDGFR-β in corpus callosum increased significantly in the 28 days after operation group, and the expression level of PDGFR-β in hippocampus decreased significantly in the 28 days after operation group and the 56 days after operation group. Compared with the 28 days after operation group, the expression of PDGFR-β in corpus callosum decreased significantly in the 56 days after operation group (P<0.05).ConclusionLearning and memory impairment caused by chronic cerebral ischemia is closely related to the structural damage of corpus callosum and hippocampus, and the alteration of PDGFR-β in the corpus callosum may be one of the key targets for predicting nerve fiber damage caused by chronic cerebral ischemia.